Medicine Meets Virtual Reality 13 : the Magical Next Becomes the Medical Now - Medicine Meets Virtual Reality 2005 : Long Beach, Calif.); Westwood, James D.; IOS Press (Amsterdam ; Washington, DC : IOS, 2005)
Robotics and intelligence networks allow the healer's sight, hearing, touch, and judgment to be extended across distance, as if by magic. The moments when scientific truth is suddenly revealed after lengthy observation, experimentation, and measurement is the real magic. This book documents these moments, which are human ingenuity in progress.
Beyond VR: creating the augmented physician -- Stiffness and texture perception for teledermatology -- Linking human anatomy to knowledgebases: a visual front end for electronic medical records -- Simulating the continuous curvilinear capsulorhexis procedure during cataract surgery on the EYESI system -- Using an approximation to the Euclidean skeleton for efficient collision detection and tissue deformations in surgical simulators -- Virtual surgical planning and CAD/CAM in the treatment of cranial defects -- New approaches to computer-based interventional neuroradiology training -- CAD generated mold for preoperative implant fabrication in cranioplasty -- Effect of binocular stereopsis on surgical manipulation performance and fatigue when using a stereoscopic endoscope -- A dynamic friction model for haptic simulation of needle insertion -- Enhanced pre-computed finite element models for surgical simulation -- Cardiac MR image segmentation and left ventricle surface reconstruction based on level set method.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Virtual reality in medicine; Medical Informatics -- methods; Telemedicine -- methods; User-Computer Interface; Réalité virtuelle en médecine.; medicines (material); TECHNOLOGY & ENGINEERING -- Biomedical; MEDICAL -- Family & General Practice; MEDICAL -- Allied Health Services -- Medical Technology; MEDICAL -- Biotechnology; MEDICAL -- Lasers in Medicine; Virtual reality in medicine; ICT; Virtuele werkelijkheid; Medisch onderzoek; Medicine; Congress; Congresses; Fulltext; Internet Resources; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.